FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR PADA TAHUN 2016-2019 - Alverina Daria Arlis; Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this research is to obtain empirical evidence about the effects of corporate social responsibility, firm profitability, firm size, and financial leverage on financial performance in manufacturing industries listed in Indonesian Stock Exchange during the period of 2016-2019. This research used 63 samples from selected manufacturing companies with purposive sampling method. Secondary data was used in the form of financial information from the financial statements and annual reports. The data in this research were calculated with Microsoft Office 365 software and then processed with Eviews 9.0. The result in this research shows that corporate social responsibility, firm profitability and firm size have a significant effect on financial performance, while financial leverage has an insignificant effect on financial performance.